DNA free transcriptional activation using CRISPR / DCAS9 nucleoproteins to enhance the biosynthesis of steviol glycosides in stevia (Stevia rebaudiana Bertoni) - Ghose, Asish Kumar (2023)
Steviol glycosides (SGs) are responsible for the sweetness of stevia (Stevia rebaudian Bertoni) which are 100–300 folds sweeter than sucrose. Stevioside and rebaudioside A present in stevia are the most prominent and desirable SGs as natural sweetening agents endowed with various medicinal properties. In vitro regeneration offers great potential to meet commercial demand for expanding stevia cultivation. This study aims in developing an efficient in vitro propagation protocol for stevia through callus induction and evaluates the effect of nutrient content in growth media on SGs biosynthetic gene expression and production of stevioside and rebaudioside A in the leaves. In order to enhance the production of the high-value rebaudioside A, the CRISPR/dCas9 a gene activation system was investigated as a novel way of improving the production of this metabolite. The efficacy of Clorox and ethanol as surface sterilizing agents for explant (leaf segments) was investigated. The highest percentage of survivability (88.90 ± 5.55) of explants was found at 15 and 30 days after inoculation (DAI) on Murashige and Skoog (MS) media by sterilization with 30% Clorox for 5 min and 10% Clorox for 10 min, respectively. Addition of 2, 4-D (0.00 to 2.00 mg/L) and Zeatin (0.1 mg/L) was evaluated for callus induction from the leaf explants. The MS media containing 0.50 mg/L 2, 4-D and 0.1 mg/L zeatin stimulated 50% of explants to develop callus at 15 DAI while 1.50 mg/L 2, 4-D and 0.1 mg/L zeatin resulted in 76.67% callus at 30 DAI. The effectiveness of adding BAP (0.0 to 10.0 mg/L) and NAA (0.0 to 1.0 mg/L) for initiation of shoots from stevia calli was investigated. The highest shoot proliferation per callus was achieved with 10.0 mg/L 6-benzyl amino purine (BAP) in MS at 15 DAI (5.8) and 30 DAI (12.33). The highest average length of shoots was achieved with BAP (10.0 mg/L) and 1.0 mg/L naphthalene acetic acid of 4.31 cm and 6.04 cm at 15 and 30 DAI, respectively. The different strengths of MS media were utilized as rooting media. MS media (0.50 strength) induced 2.86 and 6.20 roots per shoot and produced 3.25 cm and 7.82 cm long roots at 15 and 30 DAI, respectively. The highest concentration of rebaudioside A (6.53%) accumulated in the leaves of stevia grown on 0.25 MS and this was correlated with its biosynthetic gene uridine-diphosphate-dependent (UDP)-glycosyltransferase 76G1 (UGT76G1) expression level. The dCas9 fused with VP64 as transcriptional activation domain (TAD) was produced and purified for the formation of ribonucleoproteins (RNPs) by mixing with four in vitro transcribed sgRNAs designed by online based tool, benchling. The protocol for efficient protoplasts isolation was optimized by utilizing the combinations of different cell wall degrading enzymes (cellulase R-10 and macerozyme R-10) at different concentrations. The highest protoplast yield was from leaf mesophyll of in vitro grown stevia plantlets (3.16 × 106/g of FW) using ES5 (1.25 % cellulase R-10 and 0.75% macerozyme R-10). The transcriptional activation efficiencies were evaluated from the transfected protoplasts with different RNPs through Polyethylene glycol (PEG)-mediated transfection. The highest endogenous activation of UGT76G1 gene expression was detected at 27.51-fold after 24 h of transfection with RNP30 consisting of CRISPR/dCas9-TAD with sgRNA30 and similar activation level was obtained using RNP18, RNP33, and RNP34, produced using sgRNA18, sgRNA33, and sgRNA34, respectively. Activation of UGT76G1 by RNP18 led to significant increase in the expression of the rate limiting enzyme UGT85C2 by 2.37-fold and there was an increasing trend in the expression of UGT85C2 using RNP30, RNP33 and RNP34. The results obtained from in vitro regeneration of stevia provided a protocol for high quality planting materials production for commercial cultivation. The expression of UGT76G1 can be a universal biomarker for monitoring the biosynthesis of rebaudioside A, the most desirable SGs in efforts to improve its production through growth media manipulation. Successful application of CRISPR/dCas9-TAD RNP in activating specific genes in stevia protoplasts provided a platform for gene functional studies in stevia while paving the way for production of DNA-free genetically modified crops that can improve public acceptance.